Pengaruh Minat Belajar dan Lingkungan Belajar Terhadap Prestasi Belajar Siswa Mata Pelajaran Pendidikan Agama Islam di UPT SPF SD Inpress Panaikang II/1 Kota Makassar - Asriani, Asriani; Sumiati; Pewangi, Mawardi (DIMAR: Jurnal Pendidikan Islam, 2025)
This study examines how learning interest and the learning environment influence students’ academic achievement in Islamic Religious Education (PAI) at UPT SPF SD Inpres Panaikang II/1, Makassar. Education serves a vital role in shaping knowledgeable and morally grounded learners, and in PAI, success is determined by both internal and external factors. Despite existing research on these variables, studies focusing specifically on PAI at the elementary level remain limited. Preliminary observations revealed low interest in PAI and an insufficiently supportive learning environment, underscoring the need for empirical investigation. Using a quantitative descriptive design, data were gathered through observation, questionnaires, and documentation from 38 purposively selected fifth-grade students. Analytical procedures included instrument testing, multiple linear regression, and significance testing. Results show that students’ learning interest falls within a good category, the learning environment is considered high, and academic achievement in PAI is very good. Simultaneous testing indicates that learning interest and the learning environment together significantly influence academic achievement. However, partial analysis reveals that learning interest does not have a significant standalone effect, whereas the learning environment exerts a significant positive influence. The coefficient of determination (R² = 0.243) indicates that both variables account for 24.3% of the variance in academic outcomes. The findings highlight the dominant role of external conditions in shaping PAI achievement. Enhancing supportive and interactive learning environments, supported by teacher initiatives and parental involvement, is essential for improving student performance. This study contributes to empirical understanding of the determinants of PAI learning success in elementary education.